Local barrier dysfunction identified by confocal laser endomicroscopy predicts relapse in inflammatory bowel disease. Issue 8 (24th November 2011) - Kiesslich, R; Duckworth, C A; Moussata, D; Gloeckner, A; Lim, L G; Goetz, M; Pritchard, D M; Galle, P R; Neurath, M F; Watson, A J M
Abstract : Objectives: Loss of intestinal barrier function plays an important role in the pathogenesis of inflammatory bowel disease (IBD). Shedding of intestinal epithelial cells is a potential cause of barrier loss during inflammation. The objectives of the study were (1) to determine whether cell shedding and barrier loss in humans can be detected by confocal endomicroscopy and (2) whether these parameters predict relapse of IBD. Methods: Confocal endomicroscopy was performed in IBD and control patients using intravenous fluorescein to determine the relationship between cell shedding and local barrier dysfunction. A grading system based on appearances at confocal endomicroscopy in humans was devised and used to predict relapse in a prospective pilot study of 47 patients with ulcerative colitis and 11 patients with Crohn's disease. Results: Confocal endomicroscopy in humans detected shedding epithelial cells and local barrier defects as plumes of fluorescein effluxing through the epithelium. Mouse experiments demonstrated inward flow through some leakage-associated shedding events, which was increased when luminal osmolarity was decreased. In IBD patients in clinical remission, increased cell shedding with fluorescein leakage was associated with subsequent relapse within 12 months after endomicroscopic examination (p<0.001). The sensitivity, specificity and accuracy for the grading system to predict a flare were 62.5% (95% CI 40.8% to 80.4%), 91.2% (95% CI 75.2 to 97.7) and 79% (95% CI 57.7 to 95.5), respectively. Conclusions: Cell shedding and barrier loss detected by confocal endomicroscopy predicts relapse of IBD and has potential as a diagnostic tool for the management of the disease.